2014
DOI: 10.1007/s12013-014-0098-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Pressure Oxygen Therapy on Brain Tissue Water Content and AQP4 Expression in Rabbits with Cerebral Hemorrhage

Abstract: To investigate the effects of different atmosphere absolutes (ATA) of high-pressure oxygen (HPO) on brain tissue water content and Aquaporin-4 (AQP4) expression in rabbits with cerebral hemorrhage. 180 New Zealand white rabbits were selected and randomly divided into normal group (n = 30), control group (n = 30) and cerebral hemorrhage group (n = 120), and cerebral hemorrhage group was divided into group A, B, C and D with 30 rabbits in each group. The groups received 1.0, 1.8, 2.0 and 2.2 ATA of HPO treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The intervention resulted in a 38.7% reduction in perihematomal edema 24 h after ICH [ 24 ]. Thus, the brain water reduction was more modest than the complete reduction achieved with 2 ATA and the 74.8% reduction with 2.2 ATA as shown previously by Wu et al at 24 h after ICH in rabbits [ 21 ].…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…The intervention resulted in a 38.7% reduction in perihematomal edema 24 h after ICH [ 24 ]. Thus, the brain water reduction was more modest than the complete reduction achieved with 2 ATA and the 74.8% reduction with 2.2 ATA as shown previously by Wu et al at 24 h after ICH in rabbits [ 21 ].…”
Section: Introductionsupporting
confidence: 64%
“…These authors found that HBO at 2 ATA exerted an optimal effect. At 2 ATA, the excess in brain tissue water content over the sham level was reduced by 67.7% on day 3 and 79.5% on day 5 as compared to the untreated control [ 21 ]. The HBO at other pressures (1.8 ATA and 2.2 ATA) reduced brain water content by about 40% on the third and fifth days.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations